2014
DOI: 10.1186/1750-9378-9-27
|View full text |Cite
|
Sign up to set email alerts
|

The GH-IGF-SST system in hepatocellular carcinoma: biological and molecular pathogenetic mechanisms and therapeutic targets

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common malignancy worldwide. Different signalling pathways have been identified to be implicated in the pathogenesis of HCC; among these, GH, IGF and somatostatin (SST) pathways have emerged as some of the major pathways implicated in the development of HCC. Physiologically, GH-IGF-SST system plays a crucial role in liver growth and development since GH induces IGF1 and IGF2 secretion and the expression of their receptors, involved in hepatocytes cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 200 publications
(251 reference statements)
3
20
0
3
Order By: Relevance
“…primarily in the liver, liver IGF-I knockout mice had 70% reduced plasma IGF-I (Sjögren et al, 2001) (Britt-Marie Iresjö1 2013. It is reported that, hepatic IGF-I acted directly on the hepatocytes in a GH-independent manner, regulated hepatocytes cell proliferation, differentiation and metabolism (Takahashi., 2012;Pivonello et al, 2014). Present observation agree with this, KDF treatment did not change the level of HDL, LDL, TC, TG and BG, but it dramatically increased the mRNA expressions of PCK, G6PC, and FBPase in liver, which are the key regulatory enzymes for hepatic gluconeogenesis (Ghafoory et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…primarily in the liver, liver IGF-I knockout mice had 70% reduced plasma IGF-I (Sjögren et al, 2001) (Britt-Marie Iresjö1 2013. It is reported that, hepatic IGF-I acted directly on the hepatocytes in a GH-independent manner, regulated hepatocytes cell proliferation, differentiation and metabolism (Takahashi., 2012;Pivonello et al, 2014). Present observation agree with this, KDF treatment did not change the level of HDL, LDL, TC, TG and BG, but it dramatically increased the mRNA expressions of PCK, G6PC, and FBPase in liver, which are the key regulatory enzymes for hepatic gluconeogenesis (Ghafoory et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, treatment with βI promoted an increase in the expression of miR‐34a relative to the CO group, which shows that βI is also capable of modulating this tumor suppressor miRNA in the promotion phase of hepatocarcinogenesis. Igf2 , the target of miR‐34a, frequently shows increased expression in HCC cells and plays an important role in the process of metastasis . In this study, we observed lower expression levels of this gene in pPNLs from animals treated with βI relative to the CO group.…”
Section: Discussionsupporting
confidence: 51%
“…The target gene Igf2 , which shows increased expression in HCC cells and plays an important role in the dissemination of neoplastic cells, was also analyzed . In this study, no differences were found in the expression of this gene in the surrounding tissues between the βI and CO groups ( P > 0.05; Figure A).…”
Section: Resultsmentioning
confidence: 74%
“…En este caso, el hígado sintetiza la mayoría del IGF-1 circulante en respuesta al estímulo de la hormona de crecimiento (GH), principal mediador del crecimiento postnatal. La GH es producida por la hipófisis anterior y su secreción de manera pulsátil está en parte controlada por dos neuropéptidos hipotalámicos, la hormona liberadora de la hormona de crecimiento (GHRH) y la somatostatina (SS) (5). La GHRH actúa estimulando la síntesis y secreción de GH, mientras que la SS la inhibe.…”
Section: Factores De Crecimiento Similares a La Insulinaunclassified